Depression among Brazilian youth: an investigation based on subgroup discovery (Research, Society and Development, 2022)
This paper investigated groups of socioeconomic and lifestyle characteristics related to depression among Brazilian youth using a data mining-based approach. Depression is the result of the complex interaction between a large number of environmental and genetic factors. However, environmental factors contributing to depression is still an open challenge. A recent and voluminous source of data with the potential to investigate these environmental factors is the National Health Survey (PNS), a study carried out periodically by the Brazilian Institute of Geography and Statistics (IBGE) which aims to produce data on the health situation and lifestyles of the Brazilian population. In this sense, we use Subgroup Discovery on the PNS in order to find sets of characteristics that make a target group stand out from others (e.g. people with depression from others).